Iron status of full-term infants in early infancy is not associated with maternal ferritin levels nor infant feeding practice. Issue 8 (28th April 2022) - Chan, Kate C.; Tsun, Joseph G. S.; Li, Albert M.; Tam, Wing Hung
Abstract: Iron deficiency (ID) in early life is associated with morbidities. Most fetal iron required for infant growth is acquired in the third trimester from maternal iron store. However, how prenatal iron level affects ferritin level in early infancy remains controversial. This study aimed to examine the associations between maternal ferritin levels and cord blood serum ferritin (CBSF) and to compare the ferritin levels between different feeding practices in early infancy. Healthy Chinese mothers with uncomplicated pregnancy and their infants were followed up at 3 months post-delivery for questionnaire completion and infant blood collection. Infants who were predominantly breastfed and those who were predominantly formula fed were included in this analysis. Serum ferritin levels were measured in maternal blood samples collected upon delivery, cord blood and infant blood samples at 3 months of age. Ninety-seven mother–baby dyads were included. Maternal ID is common (56 %) while the CBSF levels were significantly higher than maternal ferritin levels. Only three infants (3 %) had ID at 3 months of age. There were no significant correlations between maternal ferritin levels with CBSF ( r 0·168, P = 0·108) nor with infant ferritin levels at 3 months of age ( r 0·023, P = 0·828). Infant ferritin levels at 3 months were significantly and independently associated with CBSF ( P = 0·007) and birth weight ( P < 0·001) after adjusting for maternal age, parity, maternal education, infant sex and feeding practice. In conclusion, maternal ID was common upon delivery. However, maternal ferritin levels were not significantly associated with CBSF concentrations nor infant ferritin concentrations at 3 months of age.